Performance of Nursing Students with a Graphic Novel and a Collaborative Quiz Competition: A Quasi-Experimental Study - Olga Navarro-Martínez; Josep Silva; Vanessa Ibáñez-del Valle (MDPI AG, 2023)
Very few studies analyzing the benefits of gamification in nurse training exist. In this work, we assessed the impact of a quiz group competition and a collective review of a graphic novel on students' performance, specifically for future nurses during their training. The study was implemented in a geriatric care course for second-year nursing students (n = 63). The effects of gamification were measured with objective (final grades) and subjective (self-evaluation) measures. The average grade of the students who participated in the gamification trial was 12.28% higher than the average grade of the students who did not participate. The final grade was positively correlated with the number of rounds of quizzes played and the score obtained in these quiz activities. Overall, 81.8% of the students indicated that the quizzes helped them to learn. This study provides evidence that gamification can improve student performance in nurse training.